THE INFLUENCE OF MOTIVATION, COMMUNICATION, AND WORK ENVIRONMENT ON REMOTE WORK SATISFACTION IN TELECOMMUNICATION COMPANY - Ubaidillah, Ahmad Sulthon; Hadi, Syamsul; Septyarini, Epsilandri (International Conference on Humanity Education and Society (ICHES), 2024)
This research is to determine the influence of Motivation, Communication and Work Environment on Remote Work Satisfaction at the Yogyakarta Telecommunication Company where there are motivation problems among co-workers, resulting in a lack of good communication between fellow employees. The method used to collect data is by distributing questionnaires by distributing questions arranged in one collection to respondents. The next method is to collect data by observing or reviewing carefully and directly at the research location to determine the conditions that occur. The population of this research is employees at one of the Yogyakarta Telecommunications Companies, totaling 82 employees. The sampling technique uses Accidental Sampling, namely random sampling and analysis using SPSS 23. Based on the results of the research conducted, it can be concluded that there is a significant positive influence between motivation and the work environment on Remote Work Satisfaction in PT employees. Telecommunications Yogyakarta and there is communication that is not significantly positive towards Remote Work Satisfaction among PT employees. Yogyakarta Telecommunications.